(3OjhGf XGaQ GdMOGOs - (3CHhefUhQ XGaQ Hf GdbGSe Hf efUhQ Hf YHO Gddg Hf Nda Hf YHO GdZfj GdLPGej GdeYQha HGdMOGO,J (B529 (3g` s ((3eMeO Hf GdTjN WGgQ GdSeGhj s)
(3ChdgG (B:s
(3bGd aj GdhYX hGdRgO(B: (3jGHfj GdgGdcjf gd ef haGA dce ef eUGQY GdBHGA EPG eG GdkChd LaJ aeG jrW SeY aQY ef HYOg aj GdHbGA s
(3BNQgG (B:s
(3djgf aDGOj Cfg bO SdGce hBef ef Nha GdbWH hGdUO bO fLR OjhGf XGaQ GdMOGO hHYV fKQg s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B497 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B149 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B798s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs